A Higher Order Nonresonant p ‐Laplacian Boundary Value Problem on an Unbounded Domain - Iyase, S. A.; Imaga, O. F. (Abstract and applied analysis, 2025)
In this article, we prove the existence of at least one solution to the nonresonant higher‐order p ‐Laplacian boundary value problem of the form: with the nonresonant condition . We employ the Leray–Schauder continuation principle and some apriori estimates to obtain our result. MSC2010 Classification: 34B10, 34B15